Cognición epistémica y comprensión de múltiples documentos: descripción de las representaciones de estudiantes de nivel secundario desde un modelo multidimensional (Investigaciones) - Berríos Molina, Carlos (2021)
We live in a society where we can access to multiple documents by pressing one button. In this epistemic scenario, we can benefit ourselves by achieving deep learning through the comprehension of multiple documents. But we also have a problem, because a lot of the documents we find have a low quality. In this respect, epistemic cognition appears as an aspect of cognitive, affective and ethical development that guides people’s thinking. In this descriptive-exploratory study, we identify and describe categories and dimensions of epistemic cognition in a group of students while they resolve a problem related to the multiple documents comprehension.